The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1021/jp020811k
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Butylbenzene Isomers on Zeolite HBeta:  Methanol-to-Olefins Hydrocarbon Pool Chemistry and Secondary Reactions of Olefins

Abstract: The reactions of n-butylbenzene, isobutylbenzene, sec-butylbenzene, and tert-butylbenzene on zeolite HBeta (SiO 2 /Al 2 O 3 ) 150) were studied at 350°C using a pulse reactor with GC-MS analysis of product gases. Similar experiments also probed the reactions of butylbenzene isomers with excesses of methanol-13 C. The reactions of tert-butylbenzene were also explored as a function of zeolite acid site density and reactant loading. In the absence of secondary reactions such as oligomerization and cracking, olefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 26 publications
0
36
0
5
Order By: Relevance
“…[9][10][11][12][13]. Several independent studies have concluded that methylbenzenes and their protonated analogues are main pool constituents in various catalysts (H-SAPO-34, H-ZSM-5, H-Beta) [7,[14][15][16][17][18][19][20][21][22][23][24][25][26], and further that the number of methyl groups on the main methylbenzene intermediate is limited by topology [9,14,23,[27][28][29]. It has recently been shown that the higher methyl benzenes in wide-pore zeolite H-Beta give a high selectivity to propene and butene, while the lower methyl benzene analogues in H-ZSM-5 give a high selectivity to ethene and propene [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13]. Several independent studies have concluded that methylbenzenes and their protonated analogues are main pool constituents in various catalysts (H-SAPO-34, H-ZSM-5, H-Beta) [7,[14][15][16][17][18][19][20][21][22][23][24][25][26], and further that the number of methyl groups on the main methylbenzene intermediate is limited by topology [9,14,23,[27][28][29]. It has recently been shown that the higher methyl benzenes in wide-pore zeolite H-Beta give a high selectivity to propene and butene, while the lower methyl benzene analogues in H-ZSM-5 give a high selectivity to ethene and propene [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism explains formation of alkenes through an indirect route rather than direct coupling of methanol molecules. Detailed studies on the identity and activity of the hydrocarbon pool species have shown that polymethylbenzenes (methylated benzene molecules) act as the main reaction centers for the MTH reaction [9,[15][16][17][18][19][20]. Unlike Dessau's mechanism, light alkene formation including ethene from the hydrocarbon pool species is well documented and there is general consensus about the importance of the hydrocarbon pool mechanism over a limited number of materials studied so far [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have concentrated on converting methanol to hydrocarbons such as methanol to gasoline (MTG), methanol to hydrocarbons (MTH) and MTO using zeolitic catalysts such as ZSM-5 1)~3) , zeolite Beta 4), 5) , and SAPO-34 6)~8) , and the reaction paths of MTO and MTG processes over zeolitic catalysts have been reported 9) . Silicoaluminophosphate SAPO-34 (pore size ca.…”
Section: Introductionmentioning
confidence: 99%